Time course of angiogenesis and lymphangiogenesis after brief corneal inflammation. - Cursiefen, C; Maruyama, K; Jackson, D; Streilein, J; Kruse, F (2006)
PURPOSE: To study the time course of angiogenesis and lymphangiogenesis in the cornea after a short inflammatory insult. This might be helpful for the timing of corneal transplantation in high-risk eyes. METHODS: The mouse model of suture-induced inflammatory corneal neovascularization was used. After placement of 3 interrupted 11-0 sutures into the corneal stroma of BALB/c mice (left in place for 14 days), corneas were excised 2, 3, 5, 7, 14, and 21 days as well as 1, 2, 3, 6, and 8 months after surgery. Hem- and lymphangiogenesis were evaluated using double immunohistochemistry of corneas with CD31/PECAM1 as panendothelial and LYVE-1 as lymphatic endothelial marker. RESULTS: Both blood and lymphatic vessels grew into the cornea as early as day 2 after suture placement. The outgrowth was initially parallel. Hem- and lymphangiogenesis peaked around day 14. Thereafter, both vessel types started to regress. Regression of lymphatic vessels started earlier and was more pronounced than that of blood vessels. Whereas at 6 and 8 months (partly) perfused CD31+++/LYVE-1(-) blood vessels and (nonperfused) ghost vessels could still be observed, there were no CD31+/LYVE-1+++ lymphatic vessels detectable beyond 6 months after this short inflammation. CONCLUSIONS: After a temporary inflammatory insult to the cornea, there is initially parallel outgrowth of both blood and lymphatic vessels. But thereafter, lymphatic vessels regress earlier than blood vessels and are completely regressed by 6 months. Earlier regression of pathologic corneal lymph versus blood vessels suggests that corneal graft survival in high-risk eyes might best be delayed for a prolonged interval following an inflammatory insult.